The Role of Technology in Early Childhood Education : Enhancing Learning Experiences - Mulugeta Mekonnen Demeke; Zewdu Alem Gebremedhin; Tesfaye Kidane Yohannes (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
With the rise of digital technology, early childhood education is experiencing a significant transformation. This paper explores how technology tools such as interactive apps, e-learning platforms, and digital toys can enhance learning experiences in young children. The study assesses both the benefits and challenges of incorporating technology in early education, focusing on cognitive development, social skills, and creativity. The findings highlight that, when used appropriately, technology can support children's learning while fostering their curiosity and engagement.